Parallel robot prototype driven by four cables: experimental results - Aguas, Xavier; Herrera, Marco Antonio; Sotomayor, Nelson; Camacho, Oscar (Enfoque UTE, 2019)
Parallel cable robots are a special class of parallel robots which are formed by replacing rigid links with cables. Due to the characteristics provided by the cables, like low inertia and greater range of motion, this type of robots can perform a wide range of applications such as: moving cameras from one place to another in sporting events, motoring industry and mainly in rehabilitation of limbs. However, due to the unilateral property of cables, keeping them tensioned becomes a great challenge. This article describes the construction of a parallel robot driven by four cables with the aim to draw three figures through the study of the kinematic and dynamic model considering the redundancy, i.e., more cables than degrees of freedom, in order to avoid those cables that require more tension during the motion of the end-effector.